2019
DOI: 10.1002/cbic.201900453
|View full text |Cite
|
Sign up to set email alerts
|

19F NMR Spectroscopy Tagging and Paramagnetic Relaxation Enhancement‐Based Conformation Analysis of Intrinsically Disordered Protein Complexes

Abstract: The combination of 19F NMR spectroscopy tagging and paramagnetic relaxation enhancement (PRE) NMR spectroscopy experiments was evaluated as a versatile method to probe protein–protein interactions and conformational changes of intrinsically disordered proteins upon complex formation. The feasibility of the approach is illustrated with an application to the Myc‐Max protein complex; this is an oncogenic transcription factor that binds enhancer box DNA fragments. The single cysteine residue of Myc was tagged with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Moreover, results from these studies revealed that the fibril-forming path of α-Syn might occur without accumulation of soluble low molecular weight intermediates, as no new 19 F NMR signals were observed during the time-course of the aggregation process. 19 F NMR spectroscopy has also now been employed to analyse the conformational dynamics of IDPs upon tertiary and quaternary complex formation [79]. The Myc-Max heterodimer is a well-known oncogenic transcription factor complex able to bind to enhancer box (E-box) regions (5'-CACGTG-3') of DNA with low-nanomolar affinity, what triggers its biological function as a transcriptional regulator [80].…”
Section: F Nmrmentioning
confidence: 99%
“…Moreover, results from these studies revealed that the fibril-forming path of α-Syn might occur without accumulation of soluble low molecular weight intermediates, as no new 19 F NMR signals were observed during the time-course of the aggregation process. 19 F NMR spectroscopy has also now been employed to analyse the conformational dynamics of IDPs upon tertiary and quaternary complex formation [79]. The Myc-Max heterodimer is a well-known oncogenic transcription factor complex able to bind to enhancer box (E-box) regions (5'-CACGTG-3') of DNA with low-nanomolar affinity, what triggers its biological function as a transcriptional regulator [80].…”
Section: F Nmrmentioning
confidence: 99%
“…PRE measurements have also been used to show dynamic conformational effects within Myc upon Myc-Max heterodimer formation and interactions with DNA. 147 In-cell 19 F NMR The absence of 19 F in biological systems makes the transition to in-cell studies a natural advancement, as it avoids spectral background signals. Early studies were completed in the yeast S. cerevisiae by inducible expression of target proteins and labeling with 5FW to measure protein mobility in cells.…”
Section: Quantification Of Binding Interactions In Intermediate and Slow Exchangementioning
confidence: 99%
“…PRE measurements have also been used to show dynamic conformational effects within Myc upon Myc-Max heterodimer formation and interactions with DNA. 147 …”
Section: Protein-observed 19 F Nmrmentioning
confidence: 99%
“…Recently, approaches based on the site-specific introduction of paramagnetic labels could characterize the DNA-binding sites of (partially) disordered TFs [61] , [62] , [63] , [64] , [65] . These approaches employed the so-called paramagnetic relaxation enhancement (PRE) technique [66] .…”
Section: Combining Nmr and MD Simulationsmentioning
confidence: 99%